Spaced cognitive training promotes training transfer - Wang, Zuowei; Zhou, Renlai; Shah, Priti (Frontiers in Human Neuroscience, 2014)
Cognitive training studies yield wildly inconsistent results. One dimension on which studies vary is the scheduling of training sessions (Morrison & Chein, 2011). In this study, we systematically address whether or not spacing of practice influences training and transfer. We randomly assigned 115 fifth grade children to an active control group or one of four training groups who received working memory training based on a “running span” task (Zhao et al., 2011). All groups received the same total amount of training: 20 sessions of training with 60 trials for an average of 20 minutes per session. The training was spread across 2 days, 5 days, 10 days, or 20 days. The active control group received 20-minute sessions of math instruction for 20 sessions. Before and after training participants in all five groups performed a single transfer test that assessed fluid intelligence, the Raven's Progressive Matrices Test. Overall, participants in all four training groups improved significantly on the training task (at least partially), as reflected by increased speed. More importantly, the only training group to show significant improvement on the Raven's was the group who had the greatest amount of spacing (20 days group) during training and improvement in this group was significantly higher than that of the control group.